Presence of Atrial Fibrillation in Stroke Patients With Patent Foramen Ovale: Systematic Review and Meta-Analysis - Chen, Jessie Ze-Jun; Thijs, Vincent N. (Frontiers in Neurology, 2021)
Purpose: Patent foramen ovale (PFO) is associated with ischemic stroke, especially in patients with embolic stroke of undetermined source. This study aims to evaluate the presence of atrial fibrillation (AF) in ischemic stroke patients with PFO. Methods: We systematically searched EMBASE and MEDLINE databases on May 21, 2020 for studies that analyzed the presence of AF in patients with PFO. The primary outcome was the presence of AF in patients with PFO compared with those without. Outcomes were pooled using a random-effects model using the method of DerSimonian and Laird. We recorded demographic characteristics and the methods used for AF detection in the studies included (unspecified, history/medical records review, ECG, Holter monitor, or loop recorder). Results: A total of 14 studies and 13,245 patients fulfilled the entry criteria. The average age was 61.2 years and 41.3% of the participants were female. There was a lower risk of AF in patients with PFO compared with those without (RR 0.52, 95% confidence interval, 0.41–0.63, p < 0.001). There was no evidence of heterogeneity. The lower risk of AF was found in cross-sectional and longitudinal studies and in studies stratified by average age (<60 or ≥60) and in cryptogenic stroke. Meta-regression by PFO detection technique suggested that studies using transoesophageal echocardiogram for PFO detection reported higher risk of AF (1.39, 95% confidence interval 1.14–1.70, p = 0.004). Conclusion: The presence of a PFO in patients with ischemic stroke/TIA may be associated with a lower risk of AF. Few studies have estimated the risk of future AF in patients with PFO.